Bioagents for alleviation of soil moisture stress - Singh, Geeta; Singh, Devendra (Indian Farming, 2016)
Soil microorganisms with potential for alleviation of abioticstresses in combination with plant growth promotion would be extremely useful tools in sustainable agriculture. Indirect effect of PGPR is increased nutrient uptake from soils experiencing low soil moisture, thus reducing the need for fertilizers and preventing the accumulation of nitrates and phosphates in agricultural soils. A reduction in fertilizer use would lessen the effects of environmental contamination and lead to savings for farmers. These simple and low-cost alternatives need to be harnessed to improve agricultural production under the current scenarios of global climate change.